Respon Pertumbuhan Dan Hasil Tanaman Kacang Tanah (Arachis Hypogaea L.) Terhadap Pemberian Pupuk Organik Cair Buah Pada Dosis Yang Berbeda - Ferderika Hana Ndapabanjal; Marten Umbu Nganji; Suryani K. K L. Kapoe (Universitas Medan Area, 2022)
Peanut (Arachhis hypogaea L.) is an important food commodity with high economic value which is cultivated by some farmers in East Sumba Regency, because the climatic conditions are very suitable for the development of this commodity. The purpose of this study was to determine the response of giving fruit liquid organic fertilizer with different doses to the growth and yield of peanuts (Arachis hypogaea L.). This research was carried out in March – June 2021 on a land located in RT 09 / RW 03, Kambajawa Village, Waingapu City District. The design carried out in this study was a Randomized Block Design (RAK) with the application of fruit MOL fertilizer, consisting of 5 treatments: P0 = control, P1 = 25 ml/L water, P2 = 50 ml/L water, P3 = 75 ml/L water and P4 = 100 ml/L water. The parameters observed in this study included plant height, number of leaves, dry weight of the stover, number of seeds, number of pods, and weight of seeds. The results of this study showed that the best dose of liquid organic fertilizer for fruit growth and yield of peanut (Arachis hypogaea L.) was 75 ml/L of water.